Defect Engineering on CeO2‐Based Catalysts for Heterogeneous Catalytic Applications. Issue 12 (5th September 2021) - Yang, Chunming; Lu, Yuxuan; Zhang, Le; Kong, Zhijie; Yang, Tianyi; Tao, Li; Zou, Yuqin; Wang, Shuangyin
Abstract : With abundant crystal defects, cerium oxide (CeO2 ), widely used in heterogeneous catalysis, has attracted extensive attention. In recent years, researchers have investigated that the defect chemistry of CeO2 plays a vital role in its catalytic activity and have developed various defect introduction methods to synthesize stable and efficient defective CeO2 ‐based catalysts. Herein, the understanding, introduction, and applications of defect chemistry in CeO2 ‐based heterogeneous catalysis are reviewed, and the structure–activity relationship between defect engineering and catalytic performance is recommended with great emphasis. Interests are put into the investigation of how defects influence the activity and stability of defective CeO2 catalysts and effective strategies for fabricating efficient, stable, and defective CeO2 catalysts. Finally, the existing problems and perspectives of CeO2 defect chemistry for heterogeneous catalysis are displayed. This review provides a reference for in‐depth understanding and the design of more efficient CeO2 ‐based catalysts for heterogeneous catalysis. Abstract : The understanding, introduction, and application of defect chemistry in CeO2 ‐based heterogeneous catalysis are reviewed herein. The structure–activity relationship between defect engineering and catalytic performance is recommended with great emphasis. The existing problems and perspectives of CeO2 defect chemistry for heterogeneous catalysis are displayed.